Pengaruh Market to Book Value of Equity, Debt to Equity Ratio dan Dividend Payout Ratio terhadap Net Profit Margin dimoderasi Jumlah Dewan Komisaris - Jariah, Ainun (Kompartemen : Jurnal Ilmiah Akuntansi, 2021)
Financial performance an analysis carried out to see the extent which a company has financial implementation rules. The financial performance really depends on manages the company’s finances and carries out the activities, therefore is required improve its ability to manage. Financial performance can be achieved by implementing financial management which involves the completion of important decisions taken by the company, investment and funding decisions, dividend policies. To implement financial decisions properly requires the role of good corporate governance. Research aims to determine the effect of market to book value of equity (MVE/BE), debt to equity ratio (DER), and dividend payout ratio (DPR), partially or simultaneously on net profit margin (NPM) and numbers of commissioners as moderating. By multiple linear regression analysis and moderation, the results MVE/BVE and DER have a significant effect on NPM and number of commissioners. MVE/BVE, DER, and DPR simultaneously a significant effect on NPM and number of commissioners. Number of commissioners moderates the effect of DPR on NPM.